2019
DOI: 10.1111/are.14233
|View full text |Cite
|
Sign up to set email alerts
|

Using machine learning algorithms to analyse the scute structure and sex identification of sterlet Acipenser ruthenus (Acipenseridae)

Abstract: Sturgeons are valued as specialty black caviar, which is very expensive. Only females are used in the technology of caviar aquaculture. Universal method of sex determination has not yet been developed. Most of known methods are not sufficiently accurate, or used at a relatively late age, or difficult to use. Perfect early determination of sex is considered to be impossible. Because of the dark colour of most sturgeons and important morphological differences, which fish of almost all ages have, were overlooked.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…Supervised learning is used for classification and regression as a learning method with a model that maintains the object's value. Citing the theory of machine learning and its advantages, several theories have been implemented in aquaculture, for example, the detection of fish biomass [51,52], calculation of fish size [53] and weight [54][55][56], individual counting [57], fish recognition [58], age detection [59], sex detection [60], fish species classification [61][62][63], feeding behavior [64], univariate prediction [65,66], and multivariate prediction [67], with high accuracy. Regarding artificial vision processes, the documents that make intelligent diagnoses of possible fish diseases will be addressed, ensuring their well-being and health and thus preventing the death of the species.…”
Section: Artificial Vision and Image Processing In Aquaculture Systemmentioning
confidence: 99%
“…Supervised learning is used for classification and regression as a learning method with a model that maintains the object's value. Citing the theory of machine learning and its advantages, several theories have been implemented in aquaculture, for example, the detection of fish biomass [51,52], calculation of fish size [53] and weight [54][55][56], individual counting [57], fish recognition [58], age detection [59], sex detection [60], fish species classification [61][62][63], feeding behavior [64], univariate prediction [65,66], and multivariate prediction [67], with high accuracy. Regarding artificial vision processes, the documents that make intelligent diagnoses of possible fish diseases will be addressed, ensuring their well-being and health and thus preventing the death of the species.…”
Section: Artificial Vision and Image Processing In Aquaculture Systemmentioning
confidence: 99%
“…La identificación del sexo en los peces y su separación en espacios diferentes es una actividad importante que asegura la sostenibilidad de semilla para la acuicultura, mantener un plantel de reproductores machos y hembras es prioridad para proyectar la producción de semilla. Según Barulin (2019), la perfecta determinación temprana del sexo se considera imposible.…”
Section: Perspectivas De La Inteligencia Artificial En Acuiculturaunclassified
“…In addition, it has been reported that water quality parameters can be predicted with artificial intelligence applications (Yeon et al, 2008). Moreover, biomass detection (Yang et al, 2021), weight estimation (Fernandes et al, 2020), fish size estimation (Li et al, 2020) and sex identification (Barulin, 2019) can be successfully evaluated by using the ML methods.…”
Section: F I G U R Ementioning
confidence: 99%
“…Aquaculture applications with machine learning (ML) techniques have the potential to offer solutions to the problems that develop in the production process (Liakos et al, 2018; Samuel, 2000). In this regard, many studies on fish size (Li et al, 2020) and weight estimation (Fernandes et al, 2020), biomass detection (Yang et al, 2021) and sex discrimination (Barulin, 2019) were reported. Furthermore, the dissolved oxygen concentration of water (Cao et al, 2020; Huan et al, 2020; Ren et al, 2020) was successfully predicted.…”
Section: Introductionmentioning
confidence: 99%